MINIMALLY INVASIVE GLAUCOME SURGERY, TECHNIQUES AND PROCEDURES - Bogdanova, Irina; Pandilov, Stefan; Rushiti, Muhamedin (Journal of Morphological Sciences, 2024)
Minimally invasive glaucoma surgery (MIGS) are relatively new technologies that have enabled major advances in the management of glaucoma patients, providing a safer and less invasive way to address elevated IOP compared to traditional surgical techniques. The main goal of these procedures is the reduction of IOP, which is the main modifying risk factor in the progression of glaucoma, using small incisions and minimal tissue damage. Patients with mild or moderate glaucoma have the main benefit from these interventions. The short recovery period and the lower number of complications are the main advantages of these procedures compared to traditional ones. The aim of this literature review is to present the current types of MIGS with all their characteristics and the different anatomical pathways involved in intraocular pressure (IOP) reduction in glaucoma patients. Also through this paper we want to highlight the new types of MIGS, the integrated approach of MIGS with cataract surgery or digital monitoring tools in order to achieve a greater and better result in patients who need such interventions. The long-term effects of MIGS use are not yet well known. Additional research is needed that will enable more precise answers to such questions in the future, as well as the development of new devices that contribute to MIGS becoming a standard treatment in the management of glaucoma patients. Keywords :  glaucoma, MIGS, minimally invasive glaucoma surgery, intraocular pressure, surgery, glaucoma management.